The Potential of Application of Technology-Based Innovations for Zakat Administration in India - Aishath Muneeza; Shahbaz Nadwi (Center of Strategic Studies (PUSKAS) BAZNAS, 2019)
India is the home country for many Muslims and effective management of zakah is essential to the country. In this era of technology, it is imperative to use technology with zakat to ensure that the classical zakat administration approaches are upgraded to the uruf or customary practices of the society. The objective of this paper is to find out the potential of using technology in upgrading zakat administration in India. This is a qualitative approach where the primary sources such as zakat administration laws in India and secondary sources such as journal articles and published reports on the subject are analysed to derive conclusions. The findings of this paper suggest that the innovations such as rice ATMs, mobile applications, applications made with blockchain technology, artificial intelligence and big data can also play a vital role in the effective management of zakat in India. It is anticipated that the outcome of this research will assist the zakat administrators in India to adopt technology in this regard. Keywords: Artificial intelligence, big Data, fintech, rice ATM, zakat